Characteristics of drug resistance in HIV-1 CRF55_01B from ART-experienced patients in Guangdong, China. (16th April 2020) - Lan, Yun; Xin, Ruolei; Cai, Weiping; Deng, Xizi; Li, Linghua; Li, Feng; Cai, Xiaoli; Tang, Xiaoping; Fan, Qinghong; Hu, Fengyu
Abstract: Background: HIV-1 acquired drug resistance (ADR) has become a critical clinical and public health issue. Recently, HIV-1 CRF55_01B has been found more frequently in the MSM population. Objective: To investigate the characteristics of HIV-1 drug resistance mutations (DRMs) and the extent of changes in drug susceptibility among ART-experienced CRF55_01B-infected adults of Guangdong. Methods: ADR was tested for immediately in CRF55_01B-infected patients with virological failure. Demographic and epidemiological information was collected. DRMs and antiretroviral susceptibility were interpreted using the Stanford University HIV Drug Resistance Database HIVdb program. Results: Overall, 162 (4.78%) CRF55_01B isolates were identified from 2013 to 2018. Among DRMs, M184V (43.83%) was the most frequent NRTI DRM, followed by K65R (23.46%), and V179E (98.77%) was the most frequent NNRTI DRM, followed by K103N (47.53%) and Y181C (14.81%). According to the HIVdb program, 79.01% of the CRF55_01B-infected patients carried mutations conferring low-level or higher drug resistance to any of the three classes of ART drugs. Among PI DRMs, only one mutation affording low-level resistance to nelfinavir was found (0.62%). Among NRTI DRMs, a high proportion of high-level resistance to lamivudine (58.64%) and emtricitabine (58.02%) was found. As regards NNRTIs, more than 75% of patients carried efavirenz and nevirapine DRMs. The percentages of high-level resistance were 70.99%, 63.58%, 22.22%, 17.90% and 4.32% for nevirapine, efavirenz, rilpivirine, doravirine and etravirine, respectively. Conclusions: High frequencies of DRMs and resistance were observed among CRF55_01B-infected patients failing ART in Guangdong, and interventions may be considered to minimize ecological contributions to ART.